Pierre Bourdieu - Jenkins, Richard 1952- (Routledge, 2025)
"This short critical introduction to Pierre Bourdieu's thought has been comprehensively brought up to date for the third edition. Where Bourdieu's own writings are often complex, even ambiguous, Richard Jenkins is direct, concise and to the point. Emphasizing Bourdieu's contributions to sociological and anthropological epistemology, Jenkins also deals in detail with Bourdieu's substantive studies of education, social stratification, cultural consumption, language, and rural society in transition. A model of clarity and insight, this book offers an accessible introduction to Bourdieu's work for students, scholars, and all those interested in social thought"--
Keywords: Bourdieu, Pierre / 1930-2002; Sociology / France; Sociology / Methodology; Sociologie / France